PEMBERDAYAAN UNTUK MENINGKATKAN KOMPETENSI PEJABAT STRUKTURAL PEMERINTAH: Kasus di Bidang Kepegawaian di Provinsi DKI Jakarta dan Provinsi DI Yogyakarta - Djoko Sutrisno; Sumardjo Sumardjo; Pang S Asngari; Soedijanto Padmowihardjo; Prabowo Tjitropranoto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
The civil service management had to change its paradigm in appointing the structural goverment officials (SGO)’s so far the work achievement of goverment structural officials was still low. In conjunction with this, the objectives of this research were: (1) To evaluate the level of empowerment, internal organization characteristics, motivation and competency of SGO; (2) To determine the factors that influence the empowerment, competence and motivation of SGO; and (3) To formulate the model for increasing the structural geverment officials (SGO) competency. This research was accomphlished in DKI Jakarta and DI Yogyakarta. This research was a census, 163 government structural officials were interviewed. The research results pointed out that: (1) The levels of empowerment, attitudes, motivation and competency of every officials interviewed were good. Additionally, their nonformal education and organization technology was also good. (2) The non formal education, attitudes and mastering of organization technology were related to the SGO empowerment; (3) The empowerment and the motivation of SGO were significantly related to their competencies; (4) The SGO empowerment was related to the SGO motivation. Based upon these fundings, it could be concluced that all factors investigated were related to the empowerment, and on the other hand the empowerment was related to the SGO motivation and competency.